An Investigation of Hybrid Solar-Steam Power Plant: A case study in Iraq - Amori, Karima Esmail; Sari, Randa Rashid (Journal of Petroleum Research and Studies, 2020)
In this work integrating Al-Zubaydia (Kut-Iraq) thermal power plant with solar thermal system is studied for heating feed water by solar energy to reduce fuel consumption and greenhouse gases emission. A closed type Parabolic Trough Solar Collector (PTSC) is designed, constructed, instrumented, and tested. Its thermal characteristics are reported under Iraq climate conditions for the period extended from June, to September 2017. The collector heat gain, efficiency, absorber temperature and heat exchanger effectiveness (considered as feed water heater) were presented for absorber side flow rates of (0.15, 0.2, 0.3, 0.4, 0.5) lpm of water or oil), and shell side water flow rates of (0.4, 0.5, 0.6lpm). Results show that the maximum obtained thermal efficiency of parabolic trough solar collector was 83.33% for oil working fluid. The maximum obtained oil outlet temperature was 106 oC at solar noon for (0.15) lpm. Theoretical results showed that the fuel save mode needs collector area of (32842 m2), while that needed for power boosting is (102569 m2) for the same thermal cycle efficiency. The fuel save mode reported a reduction in greenhouse emission.